Quality of life and psychoemotional status in patients with external genital endometriosis - E. Begovich; A. G. Solopova; S. V. Khlopkova; E. A. Son; L. E. Idrisova (Акушерство, гинекология и репродукция, 2022)
Introduction. Chronic pain syndrome with external genital endometriosis (EGE) causes profound psychoemotional changes, anxiety disorders, decreased physical and social activity, general well-being and mood, sexual dysfunction, and as a consequence, deteriorated quality of patients' life.Aim: to study an influence of psychoemotional disorders on the quality of life of women with painful and painless forms of EGE.Material and Methods. There were enrolled 160 patients (110 women with painful and 50 with painless forms of EGE) of reproductive age with laparoscopically and morphologically verified diagnosis, according to the Revised American Fertility Society score (R-AFS) classification. Pain syndrome and psychoemotional status were assessed using various quality of life assessment questionnaires: Visual Analog Scale (VAS), Endometriosis Health Profile-30 (EHP-30), Hospital Anxiety and Depression Scale (HADS). After surgical treatment, 8 patients refused to participate in the work (6 with painful form of EGE and 2 with painless form). Thus, 152 women passed all stages of the study. The patients were divided into 4 groups depending on the presence and/or absence of pain syndrome and tactics of the rehabilitation period ("active" or "passive"): group IA consisted of 49 (47.1 %) women with pain syndrome and "active" rehabilitation; group IБ – 55 (52.9 %) women with pain syndrome and "passive" rehabilitation tactics; group IIA – 23 (47.9 %) patients without pain syndrome and with "active" rehabilitation; group IIБ – 25 (52.1 %) patients without pain syndrome and with "passive" rehabilitation tactics.Results. It was found that painful vs. painless form of EGE differs by a more severe course of the disease and markedly decreased quality of life. In a comparative analysis of the four groups it was noted that women with "active" tactics of rehabilitation measures (IA and IIA) had a decrease in pain syndrome, improved emotional, social and sexual activity, decreased depression and anxiety scores as compared to the patients (IБ and IIБ) who underwent a set of rehabilitation measures within the National clinical guidelines.Conclusion. Timely diagnostics and correction of psychoemotional disorders will allow to develop a differentiated approach to provide specialized medical and psychological care and improve the quality of life of patients with EGE.